MEMÓRIA, LINGUAGEM E HISTÓRIA NO FESTIVAL NATIVISTA - Dorneles, Elizabeth Fontoura (Organon, 2003)
The text introduces reflections about memory. We try to discoverwich is the relation between collective memory and discursivememory. In this sense, we have conceptions of history and Discourse Analysis(AD). We guide the analysis about the way how work the constructionof “gaúcha” memory, at the Nativistc Festivals.